Noise Prediction of Traction Gear of High-Speed EMU Base on Acoustic-Structural Coupled Method. Issue 1 (February 2020) - Tang, Zhaoping; Wang, Min; Wu, Yi; Zhao, Min; Zheng, Xianliang
Abstract: The dynamic characteristics of traction gear transmission system have great influence on the safety, comfort and reliability of EMU. Base on acoustic-structural coupled theory, the noise radiation characteristics of gear transmission system in high-speed train CRH380A are studied by finite element-boundary element method. The acoustic radiation analysis model is built by using acoustic BEM. The radiated noise is predicted by Helmholtz boundary integral equation. The research results can provide a theoretical basis for the optimization design of the low noise gear in EMU.